A Jonah-like chymotrypsin from the therapeutic maggot Lucilia sericata plays a role in wound debridement and coagulation. (March 2016) - Pöppel, Anne-Kathrin; Kahl, Mareike; Baumann, Andre; Wiesner, Jochen; Gökçen, Anke; Beckert, Annika; Preissner, Klaus T.; Vilcinskas, Andreas; Franta, Zdeněk
Abstract: Lucilia sericata larvae are used in maggot debridement therapy, a traditional wound healing approach that has recently been approved for the treatment of chronic wounds. Maggot excretion products (MEP) contain many different proteases that promote disinfection, debridement and the acceleration of wound healing, e.g. by activating the host contact phase/intrinsic pathway of coagulation. In order to characterise relevant procoagulant proteases, we analysed MEP and identified a chymotrypsin-like serine protease with similarities to Jonah proteases from Drosophila melanogaster and a chymotrypsin from Lucilia cuprina . A recombinant form of the L. sericata Jonah chymotrypsin was produced in Escherichia coli . The activated enzyme (Jonahm ) had a pH optimum of 8.0 and a temperature optimum of 37 °C, based on the cleavage of the chromogenic peptide s-7388 and casein. Jonahm reduced the clotting time of human plasma even in the absence of the endogenous protease kallikrein, factor XI or factor XII and digested the extracellular matrix proteins fibronectin, laminin and collagen IV, suggesting a potential mechanism of wound debridement. Based on these characteristics, the novel L. sericata chymotrypsin-like serine protease appears to be an ideal candidate for the development of topical drugs for wound healing applications. Graphical abstract: Highlights: Procoagulant activities of Lucilia sericata MEP can be attributed to the Jonah-like chymotrypsin peptidase. Recombinant Jonahm significantly reduces the clotting time of human plasma and degrades HMWK. Recombinant Jonahm substitutes for several contact phase/intrinsic clotting factors. Recombinant Jonahm degrades the ECM proteins laminin, fibronectin and collagen IV, but not collagens I and III.